Role of Integrity in the Success of Freelancing and Entrepreneurship: A Conceptual Review - Rosman Bin Md Yusoff; Abdul Ghafoor Kazi; Muzammil Muhammad Khan Arisar; Farhan Jamil; Sanil S. Hishan (International Review of Management and Marketing, 2016)
This study reveals the detailed conceptualization of integrity, ethics, freelancing, entrepreneurship, and role of integrity in the success of freelance and entrepreneurship. The paper is supported through conceptual review of an existing literature. It is found that integrity and ethics are well thought of similar but theoretically they are different; integrity is wholeness, pure, moral, and consistent characteristics; whilst the principles or set of rules within which one works are called ethics; a freelancer works on contract basis, is responsible for own-skill development, risks, commitments, business development, and maintenance of integrity in self, profession, and business; however, an entrepreneur is person who establishes a business with innovation, risk-taking and proactiveness. Current study found that the integrity is a core element for the success of any business whether it is freelancing or entrepreneurship; to main the integrity in business is an equal responsibility of both the employees and management. Furthermore, as the global culture is diverse in nature, some countries are liberal, some are under religious influence, and others are mixed cultured. Thus, the parameters for ethics and integrity may be different contextually, geographically, sociologically, and temporally. In order to further understand and determine such parameters an empirical research may be performed in future.